2020
DOI: 10.14814/phy2.14394
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol and metoprolol are both able to preserve myocardial function in type 2 diabetes

Abstract: Purpose Increasing cohorts of patients present with diabetic cardiomyopathy, and with no targeted options, treatment often rely on generic pharmaceuticals such as β‐blockers. β‐blocker efficacy is heterogenous, with second generation β‐blocker metoprolol selectively inhibiting β1‐AR, while third generation β‐blocker carvedilol has α1‐AR inhibition, antioxidant, and anti‐apoptotic actions alongside nonselective β‐AR inhibition. These additional properties have led to the hypothesis that carvedilol may improve c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…Our study found that fasting glucose, insulin, TG, CHO, and LDL-C were significantly higher in the observation group than in the comparison group; however, ISI and HDL-C were significantly lower in the observation group than in the comparison group, and the comparative differences were all statistically significant. We know that traditional β -blockers can lead to an increase in TG and CHO levels as well as abnormalities in glucose tolerance and increased insulin resistance while exerting therapeutic effects [ 28 ]. Therefore, improving 3-blockers and improving lipid and glucose metabolism become essential.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that fasting glucose, insulin, TG, CHO, and LDL-C were significantly higher in the observation group than in the comparison group; however, ISI and HDL-C were significantly lower in the observation group than in the comparison group, and the comparative differences were all statistically significant. We know that traditional β -blockers can lead to an increase in TG and CHO levels as well as abnormalities in glucose tolerance and increased insulin resistance while exerting therapeutic effects [ 28 ]. Therefore, improving 3-blockers and improving lipid and glucose metabolism become essential.…”
Section: Discussionmentioning
confidence: 99%
“…Trabecula isolation. Myocardial function was assessed in human RAA trabeculae, which were isolated and mounted in a custom-built organ bath as described previously (6,18). Trabeculae were superfused with a 37 C 1 mM Ca 2+ KHB (components as above) that was continuously oxygenated with carbogen (95% O 2 -5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Biorąc powyższe pod uwagę, w leczeniu pacjentów zarówno z zaburzeniami glikemii, jak i HF ważne jest stosowanie beta-adrenolityków przy zachowaniu dobrej kontroli glikemii, ponieważ ma to kluczowe znaczenie dla poprawy wyników klinicznych [15], [16], [17]. Wiadome jest, że starsze β-blokery w dawkach leczniczych, mogą prowadzić do wzrostu stężenia glukozy we krwi, upośledzenia tolerancji glukozy i zwiększonej insulinooporności [37], [54]. Dlatego pomimo powszechnej akceptacji potencjalnie korzystnych właściwości leków beta-adrenolitycznych w HF uważano, że cukrzyca jest względnym przeciwwskazaniem do stosowania leków z tej grupy.…”
Section: Podsumowanie I Wnioskiunclassified